Mosque Takmir Communication Strategy in Prospering Burhanuddin Mosque Medan Estate - Muhammad Walid; Winda Kustiawan (Edumaspul: Jurnal Pendidikan, 2024)
This research aims to understand the communication strategy of the mosque takmir in prospering the Burhanuddin Mosque on Jalan Purnawirawan Medan Estate. By using qualitative research methods, the methods used are qualitative descriptive, technical through observation, interviews, and documentation. The results of the study show that efforts to develop religious activities in mosques are greatly influenced by the active role of takmir in increasing religious activities, especially through the routine recitation of mothers. Support from mosque administrators, the community, and youth also plays an important role in advancing the mosque. Good coordination, cooperation, and communication between administrators are the key to success in prospering the mosque. This research provides important insights for mosque managers in improving religious activities and enriching the worship experience of worshippers.